Behind the waterfall - Interdisciplinary results from Holley Shelter and their implications for understanding human behavioral patterns at the end of the Middle Stone Age in southern Africa - (:unkn) unknown (My University, 2024)
Holley Shelter is a Middle (MSA) and Later Stone Age (LSA) site in KwaZulu-Natal, South Africa. The rock shelter is located at the intersection of three ecosystems, in a strip of the Savanna Biome between the Grassland and Indian Ocean Coastal Belt Biomes. Initial excavations in the 1950s by Gordon Cramb yielded large amounts of unifacial points and splintered pieces, as well as organic remains associated with MSA occupations. Our comparative techno-typological evaluation of this material in 2015 suggested the occupations may date to early MIS 3. We then initiated new excavations at the site using modern field methods and controlled sampling for lithic and organic material. Following the initial round of interdisciplinary analysis, we herein report the first absolute ages for Holley Shelter, a detailed technological analysis of new lithic material from the uppermost MSA layers at the site, and a preliminary study of the associated faunal remains. A set of 12 $^{14}$C dates place these occupations within a constricted chronological period dated to ∼36,000–34,000 cal. BP that overlaps with the so-called ‘final MSA’. The hornfels-dominated lithic assemblages are characterized by diverse core technologies oriented toward the production of laminar products, which include bladelets and abundant splintered pieces. The zooarchaeological analysis documents an emphasis on open grasslands that provided the bulk of the animal prey exploited by the inhabitants of the shelter, with a preference for medium-sized antelopes. Three bone retouchers, a rare occurrence in southern African MSA contexts, were identified in the faunal assemblage. The archaeological deposits at Holley Shelter reflect short-term, potentially seasonal, and specialized occupations that could be influenced by its ecological position. The archaeological material exhibits marked discrepancies with other well-dated final MSA assemblages such as those from Sibhudu, Umbeli Belli, Sibebe and Bor
Keywords: African Research